Long-Term Effects of Home-Based Family Therapy for Non-responding Adolescents With Psychiatric Disorders. A 3-Year Follow-Up - Bachler, Egon; Aas, Benjamin; Bachler, Herbert; Viol, Kathrin; Schöller, Helmut Johannes; Nickel, Marius; Schiepek, Günter (Frontiers in Psychology, 2020)
OBJECTIVE: Home-based treatment of families with low socio-economic status and multiple psychosocial problems (multi-problem families, MPFs) is gaining importance in clinical social epidemiology and health services research. The sustainability of the treatment is of special importance in order to breach transgenerational effects. METHODS: We examined outcome, effect size, and clinical significance of home-based treatment for 84 multi-problem families in a naturalistic setting. 48 of the families were available for a follow-up after 3 years. The baseline characteristics of these family systems included low collaboration, an increased family adversity index, minors with high rates of child psychiatric disorders, a high prevalence of comorbidity, low relational family functioning, and adolescents who refused any form of treatment or had unilaterally terminated different forms of treatment before. The home-based family therapy consisted of one or two face-to-face counseling sessions per week over an average of 28.8 months (SD = 19.2). The symptoms and competence of the adolescents, the caregivers, and the family structure were assessed with 13 variables. RESULTS: All variables showed significant improvement rates (pre- vs. post- treatment) with medium to high effect sizes (mean of Cohen’s d = 1.04, range = .34 – 2.18). All variables showed a sustained or even further improvement at follow-up. CONCLUSION: This study provides evidence of statistically (p), practically (d), and clinically (RCI) significant changes in symptom and competence-related variables among adolescents and caregivers in MPFs with sustainable long-term effects in the 3-year follow-up period.